Current and future concepts for the generation and application of genetically engineered CAR-T and TCR-T cells - Hiltensperger, Michael; Krackhardt, Angela M. (Frontiers in Immunology, 2023)
Adoptive cell therapy (ACT) has seen a steep rise of new therapeutic approaches in its immune-oncology pipeline over the last years. This is in great part due to the recent approvals of chimeric antigen receptor (CAR)-T cell therapies and their remarkable efficacy in certain soluble tumors. A big focus of ACT lies on T cells and how to genetically modify them to target and kill tumor cells. Genetically modified T cells that are currently utilized are either equipped with an engineered CAR or a T cell receptor (TCR) for this purpose. Both strategies have their advantages and limitations. While CAR-T cell therapies are already used in the clinic, these therapies face challenges when it comes to the treatment of solid tumors. New designs of next-generation CAR-T cells might be able to overcome these hurdles. Moreover, CARs are restricted to surface antigens. Genetically engineered TCR-T cells targeting intracellular antigens might provide necessary qualities for the treatment of solid tumors. In this review, we will summarize the major advancements of the CAR-T and TCR-T cell technology. Moreover, we will cover ongoing clinical trials, discuss current challenges, and provide an assessment of future directions within the field.